Social advertising and territorial inteligence in the context of Didymosphenia geminata propagation in Villarrica-Pucón and Pangupulli zone - Peña Galaz, Felipe Ignacio (Re-presentaciones: Periodismo, comunicación y sociedad, 2019)
Since the appearance of Didymosphera Geminata in Chile in 2010, specifically in the Futaleufú zone, is monitored by SUBPESCA, through its Fishing and Aquaculture Investigation Fund (FIPA), thus training and disseminating the effects of Didymo microalgae spread, which is present in the Biobio and Magallanes regions. It has been a focus of surveillance, detection and control, together with communication and social advertising campaigns by SERNAPESCA and private consulting organizations.The Didymo is an algae that lives in cold continental waters, thrives in a wide range of hydraulic conditions (Kilroy et al., 2005). The scientific literature describes it as a microalgae of great propagation and man as the main transmission vector. Localities of Villarrica, Pucón and Panguipulli, are areas declared with the plague Didymo in their rivers. In this scenario, an ethnographic study was prepared through observation in the mentioned locations
Keywords: Didymosphenia geminata; Chilean rivers Norpatagonicos; Territorial intelligence; Social advertising